The universe next door : the making of tomorrow's science - Chown, Marcus (New York : Oxford University Press, 2002)
Examines a dozen new scientific theories and ideas which go against common sense and reason, but that, according to eminent scientists, might just be true, exploring how these theories were developed and tested and discussing how they will affect the study of the universe.
Includes bibliographical references (p. 179-182) and index.
Booklist starred.
Wilson's Senior High School.
Adult
Keywords: Cosmology -- Popular works; Life on other planets -- Popular works; Physics -- Popular works; Cosmology; Life on other planets; Physics